The Impact Analysis of Water Body Landscape Pattern on Urban Heat Island: A Case Study of Wuhan City. (7th June 2015) - Yang, Bohan; Meng, Fen; Ke, Xinli; Ma, Caixue
Abstract : Based on the LST and the landscape metrics of water body with remote sensing technique and spatial analysis, the relationship between the mean LST and the attributes of water body was revealed via Pearson's correlation analysis and multiple stepwise regression analysis. Result showed that, in 32 class-based metrics we selected, the proportion of water body, average water body size, the isolation and fragmentation of water body, and other eight metrics have high correlation with the LST. As a resultant force, the quantity, shape, and spatial distribution of water body affect the forming of temperature. We found that the quantity and spatial pattern of city water body could be allocated reasonably to maximize its cooling effect.